Molecular mechanisms underlying the cholesterol-lowering effect of Ginkgo biloba extract in hepatocytes: a comparative study with lovastatin - Xie Zuo-quan; Liang Gai; Zhang Lu; Wang Qi; Qu Yi; Gao Yang; Lin Li-bo; Ye Sai; Zhang Ji; Wang Hui; Zhao Guo-ping; Zhang Qing-hua (Acta Pharmacologica Sinica, 2016)
Aim: To explore the molecular mechanisms underlying the cholesterol-lowering effect of a Ginkgo biloba extract (GBE). Methods: Enzyme activity, cholesterol flux and changes in gene expression levels were assessed in cultured hepatocytes treated with GBE or lovastatin. Results: GBE decreased the total cholesterol content in cultured hepatocytes and inhibited the activity of HMG-CoA reductase, as determined by an in vitro enzyme activity assay. In addition, GBE decreased cholesterol influx, whereas lovastatin increased cholesterol influx. GBE treatment induced significant increases in the expression of cholesterogenic genes and genes involved in cholesterol metabolism, such as SREBF2, as determined by cDNA microarray and real-time RT-PCR. Furthermore, INSIG2, LDLR, LRP1, and LRP10 were differentially regulated by GBE and lovastatin. The data imply that the two compounds modulate cholesterol metabolism through distinct mechanisms. Conclusion: By using a gene expression profiling approach, we were able to broaden the understanding of the molecular mechanisms by which GBE lowers cellular cholesterol levels. Specifically, we demonstrated that GBE exhibited dual effects on the cellular cholesterol pool by modulating both HMG-CoA reductase activity and inhibiting cholesterol influx.